Juridical Analysis of the Absence of Compensation Standards as the Cause of Diversion Failure - Alya Dwi Putri; Ismayana Ismayana (International Journal Labs, 2026)
This study examines the juridical implications of the absence of compensation standards in the implementation of diversion within the juvenile criminal justice system in Indonesia. Diversion, as a manifestation of restorative justice, is intended to resolve child criminal cases outside formal judicial proceedings while ensuring victim recovery and child protection. However, the lack of clear and operational compensation standards has created legal uncertainty and contributed to the failure of diversion agreements. This research aims to analyze the impact of the absence of compensation standards on the effectiveness of diversion and to formulate an ideal compensation model based on restorative justice principles. The study applies a normative juridical research method using statutory, conceptual, comparative, and case approaches. Legal materials were obtained from laws and regulations, scientific journals, legal doctrines, and relevant international restorative justice practices. The findings indicate that the absence of compensation standards causes subjective negotiations, imbalance between parties, and inconsistency in determining compensation, which ultimately increases the likelihood of diversion failure and continuation of cases to formal courts. Furthermore, the study reveals that effective compensation standards should be victim-oriented, proportional, participatory, and supported by clear implementation mechanisms. In conclusion, the establishment of structured and operational compensation standards is essential to strengthen legal certainty, improve victim protection, and enhance the effectiveness of restorative justice in Indonesia’s juvenile criminal justice system.